GAMBARAN TIPE ANEMIA PADA IBU HAMIL BERDASARKAN NILAI INDEKS ERITROSIT DI RSIA RESTU IBU TAHUN 2022 - Ismawatie, Emma; Jimat, Resi Tondho; Dewi, Yulia Ratna; Purwaningsih, Okti (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Anemia in pregnant women is a global problem that impacts both mother and fetus. Anemia in pregnancy is associated with maternal morbidity and is an indirect cause of maternal death in the entire population of pregnant women. Classification of anemia based on the erythrocyte index value is divided into normochromic normocytic, normochromic macrocytic, hypochromic microcytic and hypochromic macrocytic anemia. The erythrocyte index values ​​are divided into Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC). The aim of the research is to describe the types of anemia in pregnant women based on the erythrocyte index value at RSIA Restu Ibu Sragen in 2022. This research uses a quantitative descriptive research type with a retrospective approach. The research sample was 51 medical records of pregnant women who experienced anemia at RSIA Restu Ibu Sragen in January-December 2022 using purposive sampling. The materials and tools used were secondary data from laboratory examination results of pregnant women diagnosed with anemia which included hematocrit, hemoglobin, index erythrocytes (MCV, MCH, and MCHC), Microsoft Excel and SPSS Version 21 software. Data analysis used analysis univariate. The results of the study concluded that pregnant women who experienced anemia at RSIA Restu Ibu Sragen were aged 21-34 years with a third trimester pregnancy and were primigravida. Based on the erythrocyte index, normocytic anemia was normochromic in 18 people (35.3%), microcytic hypochromic anemia in 20 people (39.2%), and macrocytic hypochromic anemia in 13 people (25.5%). So it can be said that most pregnant women experience microcytic hypochromic anemia.